2013
DOI: 10.1038/aja.2013.84
|View full text |Cite
|
Sign up to set email alerts
|

The miRNA let-7a1 inhibits the expression of insulin-like growth factor 1 receptor (IGF1R) in prostate cancer PC-3 cells

Abstract: Reduced microRNA (miRNA) let-7a expression and the activation of insulin-like growth factor-1 receptor (IGF1R) signalling are both involved in prostate cancer and progression. In the present study, we demonstrated that the growth inhibitory effect of let-7a1 is directly related to targeting IGF1R gene expression in PC-3 cells. TargetScan predicted three potential target sites (T1, T2 and T3) of let-7a in the 39 untranslational region (39 UTR) of IGF1R mRNA. Real-time PCR, Western blot and luciferase reporter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In NSCLC cell lines, let-7a inhibits cell proliferation and invasion by interacting with K-Ras and HMGA2 [ 104 ]. Target analysis reveals that IGF1R is a target gene, one of let-7's numerous targets, and is involved in the IGF1R/RAS/MAPK/ELK1 pathway, playing major roles in cell proliferation and cell survival [ 109 ]. In ovarian cancer, it was reported that let-7e has many target genes including HMGA2, C14ofr28, LIN28B, and ARID3B, and let-7e expression is lower than in adjacent tissues [ 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…In NSCLC cell lines, let-7a inhibits cell proliferation and invasion by interacting with K-Ras and HMGA2 [ 104 ]. Target analysis reveals that IGF1R is a target gene, one of let-7's numerous targets, and is involved in the IGF1R/RAS/MAPK/ELK1 pathway, playing major roles in cell proliferation and cell survival [ 109 ]. In ovarian cancer, it was reported that let-7e has many target genes including HMGA2, C14ofr28, LIN28B, and ARID3B, and let-7e expression is lower than in adjacent tissues [ 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, bioinformatics approaches have predicted onethird of all mammalian genes to be targeted and regulated by miRNAs [25][26][27]. Previous studies have shown that aberrant miRNA expression could impact normal biological processes, resulting in PC initiation and progression [28][29][30]. However, a role of miR-323 in the carcinogenesis of PC has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In prostate cancer cells, miR let-7a targets E2F2 and CCND2 to inhibit cell proliferation [ 4 ]. We previously demonstrated that miR let-7a directly targets the 3′ UTR of the IGF1R mRNA and inhibits its expression in prostate cancer cells [ 7 ]. Although accumulating evidences indicate that miR let-7a exerts its anti-tumor activity by regulating oncogenes or tumor suppressor genes [ 8 ], the precise mechanisms of miR let-7a in the pathogenesis of human cancers still remain unclear and the full set of its regulatory substrates need to be further elucidated.…”
Section: Introductionmentioning
confidence: 99%